A abordagem CCS na formação de professores para uma escola inclusiva - Santos, Danielle Aparecida do Nascimento dos [UNESP] (2014)
This doctoral study was conducted in the Graduate Program in Education at the Faculty of Science and Technology, Paulista State University, named after Julio de Mesquita Filho (FCT/Unesp), located on Presidente Prudente campus in São Paulo. The line of research encompasses the study of practices and formative processes in education in the areas of Information and Communication Technologies (ICT) and Teacher Education. The general goal of this research is to investigate the process of design, implementation, and assessment of the Articulating Axis Inclusive and Special Education, based on the Constructionist, Contextualized and Signified (CCS) approach. It was offered in the blended course in Pedagogy at Unesp/Univesp, as part of the teachers' initial training and in-service training. The theoretical, methodological, and practical foundations of this research underlie both inclusive and special education and the issue of training teachers for the use of ICT, guided by CSS approach, which permeated not only the whole training process, but also the spiral-shaped learning curve, based on Valente (2002). The theoretical foundation for the research rationale, development, and analysis is built on such authors as Sacristán, Zabala, Mantoan, Moraes, Morin, Gatti, García, Tardif, Nóvoa, Perrenoud, Papert, Valente, Almeida, and Schlünzen. Linked to the Support Program in Special Education at Capes, the study equips the student teachers with essentials for performing the analysis of school inclusion policies and practices and for building new pedagogical practices using technological resources when elaborating the Inclusive Lesson Plans...